(untitled) ("Conference on Universal Science Research 2023", 2023)
Uzbek language as well as all other languages a method that creates expressiveness-emotionality and have means. Language them by grouping events, generally "method" we called it. That is, we called expressive-emotionality in phonetic phenomena a phonetic method, and its expression in word forms a morphological method. Based on this principle, phonetic expression of expressive-emotional expression in Uzbek lexical, morphological and syntactic methods are defined